Effectiveness of Smart Medical Diary to Manage Medical Affairs of Sri Lankan People - Senevirathna D.K.C.; Nadula J.K.D.P.; Kulathunga H.M.C.K.; Mapatuna R.M.; D. I. De Silva; Samitha Vidhanaarachci (International Journal of Engineering and Management Research, 2022)
In this research paper we are proposing an application that can be used to manage people's medical affairs in an organized manner. This article included what research methods we used and what results we gathered from those methods. It also includes the existing problems we identified when managing medical affairs. This paper also includes what tools and technologies and software development methods we used to develop the proposed system. Our proposed system allows patients to manage their medical appointments and medications in a highly organized manner. In this system we introduce a new functionality where users can share their personal medical records with other parties (doctors) through an access token. This access token method is very secure, and the creator of the token has full authority. In summary, this research paper contains how we gathered our requirements and how we identified existing problems that users faced when managing their medical records, what are the existing applciations in the same domain and what are the advantages and limitaions of those applications, how we developed the proposed system, what are the tools and technologies we used to develop and maintain the developmenet process of the proposed system, and how the system will make people's lives easier.